WORK PASSION AND EMPLOYEES’ CREATIVITY: THE NIGERIAN EXPERIENCE (Intent Research Scientific Journal, 2023)
This study investigates the relationship between work passion and employee creativity. The sample comprised 245 randomly selected academic staff members (including both teaching and non-teaching personnel) from five purposively selected Federal Government-owned universities in the Niger Delta Region of Nigeria. A quasi-experimental research design was employed, with data collected through a cross-sectional survey, which was considered the most appropriate method for research in administrative sciences. The Kendall Coefficient of Concordance, analysed using the Statistical Package for Social Sciences (SPSS) version 25, was utilised for data analysis. The findings reveal a positive and statistically significant relationship between work passion and employee creativity within Nigerian universities. Specifically, employees' harmonious passion for work was found to have a positive and significant influence on various measures of employees’ creativity, including expertise, creative thinking skills, and intrinsic task motivation. In contrast, employees' obsessive passion for work demonstrated a positive, albeit weak, significant influence on these measures of employees’ creativity. Based on these findings, the study concludes that employees' harmonious passion significantly enhances their creativity within the Nigerian university system. In contrast, obsessive passion appears to be relatively weak in enhancing creativity within the Federal Government-owned universities in the Niger Delta Region of Nigeria. In light of these results, university management should actively promote work passion among employees, which can foster creativity within the institution. The study also discusses additional theoretical and managerial implications for effectively managing employees' work passion and enhancing creativity in Nigerian universities.